Tick (✓) the correct answer

Question:

Tick (✓) the correct answer

If (23x − 1 + 10) ÷ 7 = 6, then x is equal to

(a) −2

(b) 0

(c) 1

(d) 2

Solution:

(d) 2

$\left(2^{3 x-1}+10\right) \div 7=6$

$\Rightarrow \frac{\left(2^{3 x-1}+10\right)}{7}=\frac{6}{1}$

$\left(2^{3 x-1}+10\right) \times 1=6 \times 7=42$

$\Rightarrow 2^{3 x-1}=42-10$

$\Rightarrow 2^{3 x-1}=32$

$\Rightarrow 2^{3 x-1}=2^{5}$

$\Rightarrow 3 x-1=5$

$\Rightarrow 3 x=6$

Therefore, $x=2$

 

Leave a comment

None
Free Study Material